Foliar magnesium application improves sweet corn yield: boosting nutrient uptake and grain carbohydrate under dense planting condition - Ye, Delian; Yu, Zexun; Chen, Jiajie; Wei, Sifan; Zhang, Zifeng; Huang, Siyu; Su, Da; Liu, Tiedong; Muneer, Muhammad Atif (Frontiers in Plant Science, 2025)
Magnesium (Mg) plays a critical role in regulating yield and grain quality in corn. However, its management is often overlooked in cultivation, particularly under high-density planting conditions, where intensified nutrient competition can exacerbate Mg deficiency. To address the knowledge gap in Mg management strategies, we conducted three-season field trials (2021-2022) evaluating foliar spraying with different concentrations of Mg fertilizer under dense planting conditions. The results showed that foliar spraying with 4% Mg significantly increased sweet corn fresh ear yield, ear weight, grain fresh weight, and grains per ear, while reducing the abortion rate compared to the foliar water spraying (CK) treatment across all three seasons. Foliar spraying with 4% Mg markedly increased dry matter, N, K, Ca, and Mg accumulation in sweet corn over two seasons in 2022. The ear leaf Soil Plant Analysis Development (SPAD) value under 4% Mg treatment increased by an average of 6.9% and 9.3% at the R1 and R3 stages, respectively, compared to CK treatment. Although 21.1% of total Mg accumulation (16.9 kg ha−¹) was acquired at post-silking, vegetative remobilization contributed minimally to total Mg (< 5%). The 4% Mg treatment significantly increased the grain filling rate at 7 and 12 days after silking, and increased grain sucrose, fructose, and glucose concentrations by an average of 14.4%, 2.7%, and 9.3%, respectively, at 27 days after silking compared to CK treatment. Based on these findings, we propose a practical Mg fertilization guideline for high-density sweet corn cultivation: three foliar applications of 4% MgSO4·7H2O, totaling 8.78 kg Mg ha-1. This strategy improves nutrient uptake, enhances grain carbohydrate accumulation, and supports yield optimization without compromising grain quality.